Reliability of the Method for Determination of Coefficient of Consolidation (cv) - Agus Setyo Muntohar (HATTI dan Universitas Udayana, 2009)
Many curve-fitting procedures based on the Terzaghi uncoupled consolidation theory have been proposed for determination of the laboratory coefficient of primary consolidation (cv). Six available methods are used in this study to evaluate the coefficient of consolidation for an expansive clay soil in Yogyakarta, Indonesia. This paper presents cv values obtaining from Casagrande's logarithm of time, Taylor's root of time, the early stage of log-t, the inflection point, the 60 t and the 45 t root of time method. A correlation between the value of cv and pressure shows that the larger variability of cv was found if the applied pressure was lower than 5 kPa. Beyond this pressure, the variability of cv was quite small and very close together. In general, the early stage of log-t method gives higher values than other methods and lower, whereas, the inflection point method have a lowest cv values among others. At higher applied pressure, four methods; Taylor’s 90 t method, Feng and Lee 60 t , Robinson and Allam's 45 t , and Mesri et. al inflection point method; give quite consistent cv value that close to the best fit line. Regardless of this fact, the data and conclusions presented address important findings for uses of the cv method for practical range of interest.